Development of Effost (English Fun for Study) Media in English Subjects of Class 10 at Ma Al Ihsan Kalikejambon - Briliansah, Tri Zanis; Rohmah, Hidayatur (Universitas Muhammadiyah Gorontalo, 2024)
This study aims to determine how students respond to application-based learning media in English subjects. This study uses questionnaires and observations as data collection techniques. The sample used in this study is students at MA Al Ihsan Kalikejambon, with a total of 20 people. The method used is development research by referring to the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The assessment instrument consists of three parts: (1) a validity assessment instrument, (2) practicality instruments in the form of questionnaire responses, and (3) an effectivity assessment instrument in the form of questionnaire responses. Based on data analysis, the first subject matter expert validation result was 88% (very feasible), the second subject matter expert was 94% (very feasible), and the media expert validation result was 86% (very feasible). The learning media has met the criteria of being very feasible, with 84.6% of student responses. Based on the study results, it can be concluded that the learning media developed based on PowerPoint Ispring Suite 11 in English subjects is very feasible.Keywords: development; learning media; English